Teacher Creativity in Classroom Management to Improve Students' Learning Ability - Neng Lia Yulianengsih (Program Studi PGMI STAI Daruttaqwa Gresik, 2023)
The purpose of this research is (1) to find out how much the correlation between the creativity of Islamic Religious Education teachers and student achievement. (2) To find out how big the correlation is between the ability to manage classes with student achievement. (3) To find out how big the correlation is between the creativity of Islamic Religious education teachers and the ability to manage classes with the learning achievement of class V Islamic Religious Education students at Lengkong Kuningan 3 Public Elementary School. The data collection techniques used were: Questionnaire Distribution, Observation, and Documentation, then after all the data was obtained, it was analyzed with SPSS 16.00 for windows. The results showed that the creativity of Islamic religious education teachers and the ability to manage classes had an effect of 30.56% on student achievement in the field of Islamic religious education at Lengkong Kuningan 3 Public Elementary School, while the other 60.54% based on observations were influenced by several factors, including internal and external factors.